Do Young Chinese Children Gain Anthropomorphism after Exposure to Personified Touch-Screen and Board Games? - Li, Hui; Hsueh, Yeh; Wang, Fuxing; Bai, Xuejun; Liu, Tao; Zhou, Li (Frontiers in Psychology, 2017)
Research shows that preschoolers are likely to anthropomorphize not only animals, but also inanimate toy after being exposed to books that personify these objects. Can such an effect also arise through young children’s use of touch-screen games? The present study is the first to examine whether playing a touch-screen personified train game affects young children’s anthropomorphism of real trains. Seventy-nine 4- and 6-year-old children were randomly assigned to play either a touch-screen game or a board game of Thomas the Tank Engine for 10 min. They completed the Individual Differences in Anthropomorphism Questionnaire–Child Form (IDAQ-CF) (two subscales: Technology/Inanimate Nature, Animate Nature) and an additional four items about the anthropomorphism of real trains, before (T1) and after (T2) the game. Overall results showed that children manifested a small but statistically significant increase in anthropomorphizing of real trains after their exposure to both games, claiming that real trains were like humans. Interestingly, 4-year-old children in the board game group tended to anthropomorphize real trains more than those in the touch-screen group, whereas the reverse was true for the 6-year-old children. The results suggest that touch-screen games may delay the decline of children’s anthropomorphism during the cognitive and socio-emotional transition that occurs in children aged 5–7. These findings have implications for future research on how touch-screen games increase children’s anthropomorphism of the real world, and more generally, for evaluation of the influence of the growing use of touch-screen games on young children’s learning.